Hubungan Personal Hygiene Dengan Gejala Peyakit Kulit Skabies di Pondok Pesantren Al-Falah Kota Padang - vitratul ilahi, Vitratul Ilahi; Oktamianiza; Rahmadhani; Yulva Yulia; Siti Handam Dewi; Dimas Maulana Syafeli (Jurnal Amanah Kesehatan, 2025)
A dormitory residential buildings inhabited by sudent. A resident is supposed to have its influences for people health related to their health behavior and availability of basic sanitation facilities. Conditions dormitory dense residential and moist can cause skin health complaints at the dormitory. To see Whether there is a relationship between personal hygiene and symptoms of the skin disesase Scabies. This research used analytic descriptive design with cross sectional appoarch which is done in pondok pesantren AL-Falah Padang December 2024. The population in the study were 196 people with a sample of 66 respondents. The data were collected through interview by using questionnaire and observation with checklist list. Univariate and bivariate data analysis using “chi square” statistic test. The result of the study show are 81,8% of respondents has symptoms of scabies, 71,2% of respondents has bad personal hygiene and a meaningful relationship between personal hygiene (p=0,029) with symptoms of scabies. The manager of dormitory was expected to give more concern to serve basic sanitation facilities which meet the health requirements, especially on crowded room occupancy. It was expected to the inhabitants to keep personal hygiene and to use basic sanitation facility well to avoid skin diseases and for those who had skin health complaints to have medical treatment.